Membrane Vesicles Derived From Clostridium botulinum and Related Clostridial Species Induce Innate Immune Responses via MyD88/TRIF Signaling in vitro - Kobayashi, Nobuhide; Abe, Kimihiro; Akagi, Sachiyo; Kitamura, Mayu; Shiraishi, Yoshitake; Yamaguchi, Aki; Yutani, Masahiro; Amatsu, Sho; Matsumura, Takuhiro; Nomura, Nobuhiko; Ozaki, Noriyuki; Obana, Nozomu; et al. (Frontiers in Microbiology, 2022)
Clostridium botulinum produces botulinum neurotoxin complexes that cause botulism. Previous studies elucidated the molecular pathogenesis of botulinum neurotoxin complexes; however, it currently remains unclear whether other components of the bacterium affect host cells. Recent studies provided insights into the role of bacterial membrane vesicles (MVs) produced by some bacterial species in host immunity and pathology. We herein examined and compared the cellular effects of MVs isolated from four strains of C. botulinum with those of closely related Clostridium sporogenes and two strains of the symbiont Clostridium scindens. MVs derived from all strains induced inflammatory cytokine expression in intestinal epithelial and macrophage cell lines. Cytokine expression was dependent on myeloid differentiation primary response (MyD) 88 and TIR-domain-containing adapter-inducing interferon-β (TRIF), essential adaptors for toll-like receptors (TLRs), and TLR1/2/4. The inhibition of actin polymerization impeded the uptake of MVs in RAW264.7 cells, however, did not reduce the induction of cytokine expression. On the other hand, the inhibition of dynamin or phosphatidylinositol-3 kinase (PI3K) suppressed the induction of cytokine expression by MVs, suggesting the importance of these factors downstream of TLR signaling. MVs also induced expression of Reg3 family antimicrobial peptides via MyD88/TRIF signaling in primary cultured mouse small intestinal epithelial cells (IECs). The present results indicate that MVs from C. botulinum and related clostridial species induce host innate immune responses.